Досвід полікультурного виховання учнів у школах США: рекомендації для вітчизняних освітян - Світлана Лук'янчук (Pavlo Tychyna Uman State Pedagogical University, 2013)
У статті здійснено узагальнення результатів дослідження полікультурного виховання учнів американської середньої школи. Визначено зміст, основні форми та методи реалізації зазначеного процесу, які представлено в авторській моделі. Подано рекомендації щодо використання позитивного виховного досвіду освітян США в загальноосвітніх навчальних закладах України. В статье осуществлено обобщение результатов исследования поликультурного воспитания учащихся американской средней школы. Определено содержание, формы и методы реализации этого процесса, которые представлены в авторской модели. Предложены рекомендации по использованию положительного воспитательного опыта педагогов США в общеобразовательных учебных заведениях Украины. The article explores the problem of pupils' multicultural education at the US secondary schools. It examines the content, forms and methods of multicultural education at the American secondary school. The research results provide evidence to the fact that multicultural education at the US secondary school is realized in the teaching and educational process, as well as extracurricular and afterschool activities. This is possible due to the implementation of educational strategies based on group-work and development of the curriculum and instructional materials with a strong multicultural component. The research claims that the role of parents, family and community in pupils' multicultural education is rather significant. It proves that effective multicultural education requires an overall school reform, with significant changes in the curriculum, teaching strategies and school policy. The generalization of the research results on pupils' multicultural education at the American secondary school are presented in the author's model. Analyzing the process of multicultural education at the American secondary school, the article works out recommendations on using the US positive experience to develop multicultural education in Ukraine. In this context it is of vital importance to get state support for innovations. It is also crucial to join the efforts of formal and informal school program in the field of multicultural education, develop appropriate methodological recommendations, education programs, textbooks and lesson plans with multicultural component, increase the interdisciplinary relations between the subjects, and implement effective educational strategies based on group-work. It is very important to develop school's cooperation with parents, volunteers, public organizations, and local authorities in the field of multicultural education. The prospects of the author's further research are the peculiarities of teaching staff management and prospective teachers' training and their role in pupils' multicultural education at the US comprehensive schools.